Development and application of a real-time RT-PCR assay to rapidly detect H2 subtype avian influenza A viruses. (May 2021) - Xiao, Yixin; Yang, Fan; Liu, Fumin; Yao, Hangping; Wu, Nanping; Wu, Haibo
The H2 subtypes of avian influenza A viruses (avian IAVs) have been circulating in poultry, and they have the potential to infect humans. Therefore, establishing a method to quickly detect this subtype is pivotal. We developed a TaqMan minor groove binder real-time RT-PCR assay that involved probes and primers based on conserved sequences of the matrix and hemagglutinin genes. The detection limit of this assay was as low as one 50% egg infectious dose (EID50 )/mL per reaction. This assay is specific, sensitive, and rapid for detecting avian IAV H2 subtypes.